Towards a transcript map of 4q32--q34 - Traulsen, Kathryn E. A (University of Ottawa (Canada), 2003)
With the completion of the sequencing of the human genome near, the next phase will be to identify and annotate all transcriptional units. We have utilized a procedure that directly selects cDNA from genomic DNA in order to isolate putative transcriptional units for identification of novel genes at the 4q34 locus. In this procedure, cDNA fragments were isolated following the hybridization of cDNA pools to 7 BAC clones spanning the 4q34 region. The 4q34 region is approximately 2.0 Mb and contains 7 known genes and 8 predicted genes. In addition, EST evidence annotated in the public databases supports the notion that there are additional transcriptional units in this region. The primary cDNA pool used in this procedure was generated with a universal primer for amplification and cloning. Approximately 350 clones were analyzed by automated fluorescence sequencing and 26 clones were shown to originate from DNA at the 4q34 locus. The other clones included rRNA, mitochondrial DNA, repetitive sequences and low-copy repeat elements, similar to the results obtained in comparable cDNA selection attempts. The tentative transcriptional units have been arranged on the current map of the 4q34 region. This map will provide insight into the organization and function of this chromosome, and provide the preliminary framework for a detailed transcription map of the region. Furthermore, novel gene identification at this locus will provide candidates for Parkinson's disease, which has been mapped to this region by our laboratory.
Keywords: Biology, Molecular.; Biology, Genetics.